Sex Differences in Motivational Traits and Ethical Decision Making among Graduating Accounting Majors - Doty, Ed; Tomkiewicz, Joe; Bass, Kenneth (College student journal, 2005)
This study is an empirical examination of possible differences between female and male accounting majors' managerial motivational traits, perceptions of ethical issues, ethical judgments, and ethical behavioral intentions regarding ethically equivocal business situations. Subjects were presented with two scales to measure their motivational traits, two ethically equivalent scenarios, and scales to measure perceptions of ethical issues, ethical judgments, and ethical behavioral intentions. Male subjects scored significantly higher than females on managerial motivational traits. Also, male respondents viewed both scenarios as significantly more unethical than females. Further, males indicated that they would be more likely than females to engage in the behaviors presented in the ethically equivocal scenarios. Implications of these findings are presented as they relate to fewer women accounting firm partners than men. (Contains 5 tables.)